1999
DOI: 10.1002/(sici)1097-0142(19990815)86:4<589::aid-cncr7>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Association between high serum alanine aminotransferase levels and more rapid development and higher rate of incidence of hepatocellular carcinoma in patients with hepatitis C virus-associated cirrhosis

Abstract: BACKGROUND Many studies have demonstrated in animal experiments that persistent inflammation may accelerate the development of carcinoma. In this article, the question of whether the persistent elevation of serum alanine aminotransferase (ALT) levels (which represents the inflammatory necrosis of hepatocytes) correlates with the development of hepatocellular carcinoma (HCC) was studied in patients with early stage hepatitis C virus (HCV)‐associated cirrhosis. METHODS Sixty‐nine consecutive patients with biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 24 publications
(26 reference statements)
5
98
1
Order By: Relevance
“…The current finding that plasma ADAMTS13 activity or antigen level significantly correlated with serum AST and ALT levels may explain this. Of note, it was previously shown that the higher serum ALT is associated with the higher rate of incidence of HCC development (31) and HCC recurrence after the surgical treatment (32) in HCV-related cirrhosis, suggesting that more hepatocellular damage increases a risk for HCC development in the liver of the same stage of fibrosis. Because plasma ADAMTS13 activity or antigen level reflect hepatocellular damage and subsequent wound healing as well as liver fibrosis stage, plasma ADAMTS13 activity, or antigen level may act distinctly from liver stiffness value in the risk analysis of HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…The current finding that plasma ADAMTS13 activity or antigen level significantly correlated with serum AST and ALT levels may explain this. Of note, it was previously shown that the higher serum ALT is associated with the higher rate of incidence of HCC development (31) and HCC recurrence after the surgical treatment (32) in HCV-related cirrhosis, suggesting that more hepatocellular damage increases a risk for HCC development in the liver of the same stage of fibrosis. Because plasma ADAMTS13 activity or antigen level reflect hepatocellular damage and subsequent wound healing as well as liver fibrosis stage, plasma ADAMTS13 activity, or antigen level may act distinctly from liver stiffness value in the risk analysis of HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year cumulative HCC incidence in cirrhosis is between 10% and 30% in HBV and HCV infection, depending on the geographic region, approximately 20% in hereditary hemochromatosis and 8% in alcoholic cirrhosis (Fattovich et al, 2004). Predictors of HCC in cirrhosis include the severity of liver disease determined by the ChildPugh score (Bolondi et al, 2001), the disease activity, reflected by serum transaminase activities (Benvegnu et al, 1994;Tarao et al, 1999), and some histological criteria, such as the presence of large cell changes (LCC) (Borzio et al, 1995;Ganne-Carrié et al, 1996), macronodules (Borzio et al, 2003) and markers for hyperregeneration (Donato et al, 2001;Trerè et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have been found that recurrence was mainly associated with adverse tumor factors such as tumor size, vascular invasion, and microsatellite [10][11][12][13][14]17,18] . Others demonstrated a liver function status [26][27][28][29][30][31][32]38] . Poon et al showed that tumor factors were linked to early recurrence, whereas the nontumorous liver status was linked to late recurrence [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hepatitis B surface antigen (HbsAg) and antibody to HCV in HCC patients were reported to be 63.2% and 11.2% respectively in China [25] , and coexisting cirrhosis occurred in 88.8% (888/1000 patients) for patients with small HCC [14] . The liver damage in patients with HCC after resection is also a risk factor for recurrence and prognosis [26][27][28][29][30][31][32] . Hence, a new stage accounting for both liver function and tumor extension is necessary to predict HCC prognosis.…”
Section: Introductionmentioning
confidence: 99%